Advances in economics and econometrics theory and applications : Eighth World Congress - Dewatripont, Mathias; Hansen, Lars Peter; Turnovsky, Stephen J. (Cambridge University Press, 2003)
This is the first of three volumes containing edited versions of papers and commentaries presented in invited symposium sessions of the Eighth World Congress of the Econometric Society. The papers summarize and interpret recent key developments and discuss future directions in a wide range of topics in economics and econometrics. The papers cover both theory and applications. Written by leading specialists in their fields these volumes provide a unique survey of progress in the discipline.